Sociodemographic and lifestyle factors associated with the Planetary Health diet in the Korean adult population - Ujin Lee; Subeen Kim; Eugene Kang; Heejin Lee; Soomin Lee; Jung Eun Lee; Minji Kang (PLoS ONE, 2026)
This study aimed to examine the associations of sociodemographic and lifestyle factors with adherence to the planetary health diet in the Korean adult population. A total of 25,336 participants aged ≥ 19 years who completed a nutrition survey of the 2016–2021 Korea National Health and Nutrition Examination Survey. The planetary health diet score was calculated based on the guidelines set by the EAT-Lancet Commission. Associations between the planetary health diet score and selected sociodemographic and lifestyle factors were assessed using multivariate logistic regression in men and women, separately. The planetary health diet score was dichotomized for men and women based on the median value, and the odds of being greater than the median scores were modeled as a dependent variable. The mean planetary health diet score was significantly higher in women (mean ± se, 9.51 ± 0.01) than in men (9.17 ± 0.02). Older age was associated with the planetary health diet score above the median in both men and women. The associations with marital status and smoking status, prevalence of monthly alcohol use differed by sex. Among men, being widowed and current smokers were associated with having planetary health diet scores below the median, whereas no such associations were observed in women. Women who were never married tended to be in the lower half of the diet score compared with married women, while the prevalence of monthly alcohol use was associated with the diet score above the median, but not in men. Physical activity, dietary supplement use, and body mass index were not significantly associated with the planetary health diet score in both men and women. Sociodemographic and lifestyle factors were associated with the planetary health diet in men and women. These findings may help to identify at-risk populations for nutritional screening and to develop nutritional intervention strategies and educational materials.